2014
DOI: 10.1038/jhg.2014.111
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the microRNA-1/133a cluster enhances cancer cell migration and invasion in lung-squamous cell carcinoma via regulation of Coronin1C

Abstract: Lung cancer is clearly the primary cause of cancer-related deaths worldwide. Recent molecular-targeted strategy has contributed to improvement of the curative effect of adenocarcinoma of the lung. However, such current treatment has not been developed for squamous cell carcinoma (SCC) of the disease. The new genome-wide RNA analysis of lung-SCC may provide new avenues for research and the development of the disease. Our recent microRNA (miRNA) expression signatures of lung-SCC revealed that clustered miRNAs mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 40 publications
3
67
0
Order By: Relevance
“…For example, Qiu et al [32] found that miR-133a was downregulated in gastric cancer tissues and cell lines and that overexpression of miR-133a inhibited proliferation, migration, invasion, and cell cycle progression in vitro. Mataki et al [33] reported that miR-133a was significantly downregulated in clinical lung cancer specimens and functions as tumor suppressors in lung cancer through regulation of oncogenic CORO1C. Ji et al [34] found that restoration of miR-133a expression in osteosarcoma cells significantly reduces cell proliferation, promotes cell apoptosis, and suppresses tumorigenicity via inhibiting Bcl-xl and Mcl-1.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Qiu et al [32] found that miR-133a was downregulated in gastric cancer tissues and cell lines and that overexpression of miR-133a inhibited proliferation, migration, invasion, and cell cycle progression in vitro. Mataki et al [33] reported that miR-133a was significantly downregulated in clinical lung cancer specimens and functions as tumor suppressors in lung cancer through regulation of oncogenic CORO1C. Ji et al [34] found that restoration of miR-133a expression in osteosarcoma cells significantly reduces cell proliferation, promotes cell apoptosis, and suppresses tumorigenicity via inhibiting Bcl-xl and Mcl-1.…”
Section: Discussionmentioning
confidence: 97%
“…Depending on their specific gene or lccRNA targets, miRNAs may function as oncogenes and/or tumor suppressors [7]. MiR-1 has been reported to function as a tumor suppressor in various cancers [8][9][10]. A previous report suggests that miR-1 may be a tumor suppressor in breast cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite of their short length, miRNAs have been confirmed to act vital important roles in various biological processes including glycometabolism (4), angiogenesis (5), cell growth (6) and movement (7).…”
Section: Introductionmentioning
confidence: 99%